Financial narratives and analysts behaviour - Silva, Diogo Ferreira Balão (2024)
This study analyses the impact of financial narratives, specifically tone and the number of forward-looking words, on analyst behaviour. Using a multivariate model in firms listed on the London Stock Exchange (LSE), we analyse these features on two report sections: Chairman´s Statement and CEO Review. While analyst behaviour is not explained by forward-looking words (with the exception of coefficient of variation metric), the results regarding tone are inconclusive.